2011
DOI: 10.2135/cropsci2010.08.0466
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence in Maize: Effect on Pollen‐Mediated Gene Flow by Conventional Maize Border Rows Edging Genetically Modified Maize Fields

Abstract: In addition to or as substitution for a regulated isolation distance, conventional maize {Zea mays L.) border rows at the genetically modified (GM) maize field edge are considered as fea-ŝ ible measure to ensure coexistence between GM and conventional or organic maize. Therefore, we examined the effectiveness of 9-mand 18-m-wide non-GM maize borders at the GM maize field edge on outcrossing rates into a neighboring non-GM maize field. One field experiment each was conducted in 2008 at three sites in Germany us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…However, it has to be kept in mind that with the installation of border rows the total distance between donor and recipient field was increased by 9 and 18 m, respectively. In our previous study on border rows, we found no effect of a 9-or 18-m-wide non-GM maize border at the GM field edge when the distance between GM and non-GM maize field was constantly 51 m (Rühl et al, 2011). Empirical data obtained by this study, as well as our previous studies on coexistence in maize, therefore suggest that the total size of the isolation method (border row + isolation distance) is most important for the reduction of pollen-mediated gene flow in maize.…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…However, it has to be kept in mind that with the installation of border rows the total distance between donor and recipient field was increased by 9 and 18 m, respectively. In our previous study on border rows, we found no effect of a 9-or 18-m-wide non-GM maize border at the GM field edge when the distance between GM and non-GM maize field was constantly 51 m (Rühl et al, 2011). Empirical data obtained by this study, as well as our previous studies on coexistence in maize, therefore suggest that the total size of the isolation method (border row + isolation distance) is most important for the reduction of pollen-mediated gene flow in maize.…”
Section: Discussionmentioning
confidence: 51%
“…In our previous study on border rows, we found no effect of a 9-or 18-m-wide non-GM maize border at the GM field edge when the distance between GM and non-GM maize field was constantly 51 m (Rühl et al, 2011). However, it has to be kept in mind that with the installation of border rows the total distance between donor and recipient field was increased by 9 and 18 m, respectively.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations